Analisis Pendistribusian ZIS dalam Meningkatkan Kesejahteraan Mustahik di Yayasan Indonesia Mulia Bekasi - Anisa, Silmi Kapah (Institut Agama Islam Negeri Ponorogo, 2021)
Islam requires its people to be able to set aside some of their assets to those who are entitled, including zakat, infaq and alms (ZIS). In addition, the distribution of zakat serves to help the poor in fulfilling their daily needs. Therefore, the more muzakki who pay zakat, the welfare of mustahik will increase optimally. Welfare is based on the concept of maqasid sharia which includes all aspects related to the afterlife, namely religion, soul, mind, lineage and property. This study aims to analyse the distribution mechanism of ZIS funds at Yayasan Indonesia Mulia Bekasi and the implications of the distribution on the welfare of mustahik. This research used descriptive qualitative method with primary and secondary data approach. Primary data was obtained directly through interviews. While secondary data was obtained through observation and documentation. The results of this study indicate that the distribution of ZIS funds at the Indonesia Mulia Bekasi foundation has been effective and on target so that the funds can be allocated according to the needs of each program. In addition, the distribution of zakat funds has a significant impact in improving the welfare of mustahik, especially orphans and poor people.